Redox-Induced Src Kinase and Caveolin-1 Signaling in TGF-β1-Initiated SMAD2/3 Activation and PAI-1 Expression - Samarakoon, Rohan (Public Library of Science, 2011)
BACKGROUND: Plasminogen activator inhibitor-1 (PAI-1), a major regulator of the plasmin-based pericellular proteolytic cascade, is significantly increased in human arterial plaques contributing to vessel fibrosis, arteriosclerosis and thrombosis, particularly in the context of elevated tissue TGF-β1. Identification of molecular events underlying to PAI-1 induction in response to TGF-β1 may yield novel targets for the therapy of cardiovascular disease. PRINCIPAL FINDINGS: Reactive oxygen species are generated within 5 minutes after addition of TGF-β1 to quiescent vascular smooth muscle cells (VSMCs) resulting in pp60(c-src) activation and PAI-1 expression. TGF-β1-stimulated Src kinase signaling sustained the duration (but not the initiation) of SMAD3 phosphorylation in VSMC by reducing the levels of PPM1A, a recently identified C-terminal SMAD2/3 phosphatase, thereby maintaining SMAD2/3 in an active state with retention of PAI-1 transcription. The markedly increased PPM1A levels in triple Src kinase (c-Src, Yes, Fyn)-null fibroblasts are consistent with reductions in both SMAD3 phosphorylation and PAI-1 expression in response to TGF-β1 compared to wild-type cells. Activation of the Rho-ROCK pathway was mediated by Src kinases and required for PAI-1 induction in TGF-β1-stimulated VSMCs. Inhibition of Rho-ROCK signaling blocked the TGF-β1-mediated decrease in nuclear PPM1A content and effectively attenuated PAI-1 expression. TGF-β1-induced PAI-1 expression was undetectable in caveolin-1-null cells, correlating with the reduced Rho-GTP loading and SMAD2/3 phosphorylation evident in TGF-β1-treated caveolin-1-deficient cells relative to their wild-type counterparts. Src kinases, moreover, were critical upstream effectors of caveolin-1(Y14) phosphoryation and initiation of downstream signaling. CONCLUSIONS: TGF-β1-initiated Src-dependent caveolin-1(Y14) phosphorylation is a critical event in Rho-ROCK-mediated suppression of nuclear PPM1A levels maintaining, thereby, SMAD2/3-dependent transcription of the PAI-1 gene.